2007
DOI: 10.1300/j098v08n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Taiwan's Textile and Clothing SME Response to Globalization

Abstract: A mixed-method research approach underpinned exploration of antecedents of strategies adopted by Taiwanese small mediumsized enterprises in the clothing and textiles industry to counter the negative economic effect of globalisation and the increasing competitive threat of lower-cost Chinese products. Primary data were collected from 10 case-companies. Phenomenological methods isolated the contingent variables, whereas positivistic statistical analysis quantified the extent of their perceived impact. A range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, the interview results further reveal that Bangladeshi RMG-SMEs have been pursuing centralised management with high power distance between employees and entrepreneurs'. Lower motivation in employees and lower degree of trust between entrepreneurs and managers are also a common feature, which is similar to Taiwanese RMG firms (Chen and Parker, 2007) and Ghanian firms' internationalisation (Kuada and Sørensen, 2000).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, the interview results further reveal that Bangladeshi RMG-SMEs have been pursuing centralised management with high power distance between employees and entrepreneurs'. Lower motivation in employees and lower degree of trust between entrepreneurs and managers are also a common feature, which is similar to Taiwanese RMG firms (Chen and Parker, 2007) and Ghanian firms' internationalisation (Kuada and Sørensen, 2000).…”
Section: Discussionmentioning
confidence: 73%
“…The RMG firms in Bangladesh are not necessarily high-technology oriented, but they are, of course, network dependent because of the collaborative nature of the network's linkages throughout the global value chain. Thus, e-commerce can be used as a convenient, personalistic and low-cost communication vehicle (Chen and Parker, 2007). Johanson and Vahlne (2009) point out that entrepreneurial and leadership quality is the key determinant of developing, nursing, and exploiting network benefits for internationalisation of SMEs.…”
Section: Entrepreneurial and Managerial Quality (Independent Variable)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Jasra et al (2011) in Pakistan; Uddin and Bose (2013) in Bangladesh; Lee, Sohn, and Ju (2011) in china; Hansen, Rand, and Tarp (2009) in Vietnam; Bah and Cooper (2012) in Kenya and so forth found the positive relationship between different aspects of government support and SMEs growth or performance. On the other hand, many studies confirmed an insignificant relationship (Chen and Parker 2007;Man 2014;Vixathep 2014). Also there is evidence of a negative relationship (Egena et al 2014).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Rahman et al (2019) found that government support did not play any instrumental role in increasing the financial and non-financial performance of the base of pyramid entrepreneurs in Bangladesh. Similarly, a study of Chen and Parker (2007) on Taiwanese SMEs related to clothing and textiles industry also showed that government support is not useful for improving the performance of SMEs. Moreover, study of Man (2014) in Malaysia revealed that SME sector in the country do not depend on government support for their business operations and such support do not play significant role for enhancing the performance of SMEs.…”
Section: Government Support and Small Firm Financial Growthmentioning
confidence: 99%